Tarih sahnesinden silinmek istenen bir soylu hatun: Eyüp’te medfun sâhî hatun veya çifte gelinler meselesi - (:unkn) unknown (My University, 2011)
0

In this study, we will reevaluate the tomb stones epitaphs within a türbe (mau- soleum) which became nearly legendary due to wrong interpretation and referral to wrong persons in all the publications so far. Epitaphs provide us with the most accurate, first-hand information regarding the structures they are attached to. However they may also lead to misinformation based upon wrong premises if they are not interpreted correctly. After reinterpreting the tomb epitaphs inside Sahî Hatun Mausoleum, which at- tracts attention with its extraordinary architectural design as well as the persons lying in it, we will refer to certain ambiguous epitaph interpretations and historical analysis we observe. Then we will offer relevant solutions. In short, we understand at the end of our research that the tomb dated 1850 due to misreading and incorrect abjad calculation, in fact dates back to 916/1510-1511 and that it did not belong to Crimean sisters who died before becoming brides but to Mihri Han, a descendent of Iranian Shah Family. The said mausoleum belongs to Sahî Hatun Foundation. Sahî Hatun’s full identity and date of death could not be determined clearly because her tomb epitaph has been missing. The Sahî Hatun Foundation afterward was annexed to the Eyüb Mosque Foundation. The names of the people lying next to each other in two mausoleums was meant to be erased from the minds as well as the epitaphs—probably at a time when political relations between the Ottomans and Iranians went sour.
A noblewoman facing an attempt of erasure from the history: medfun sâhî hatun or çifte gelinler (double brides) ıssue in Eyüp
Keywords: Tarih